#TITLE_ALTERNATIVE# - MUBAROQAN FITRO (NIM : 12214092), AGUNG
One very important variable in determining the volume of hydrocarbons in the reservoir is initial water saturation (Swi). There are various methods that can be used, but each method often gives different Swi. Errors in determining the value of Swi can cause errors in the calculation of the volume of hydrocarbons in the reservoir. This problem motivates the need to estimate the value of Swi which integrate data reservoirs / wells, so that the calculated value of Swi in the reservoir can be more accurate. There is a new method in determining the value of Swi, where this method integrates repeat formation tester data, logging data, laboratory data, and drill stem test data. This method uses the Brook-Correy parametric equation which is made unique for each rock type. In the previous case study, this method has been successfully tested on carbonate reservoir types and provides good results. In this study, this method is tested on a low resistivity reservoir. This method can overcome the determination of Swi errors that often occur in various types of reservoirs. The conclusion of this final task is that the method allows each data to validate each other, so that a more reliable Swi model can be constructed. This method needs to be tested in the reservoir with more complete data availability so that it can improve the use of this method in various types and conditions of the reservoir.